Distilling authentic community-led strategies to support people with dementia to live well. Issue 4 (8th August 2018) - Courtney-Pratt, Helen; Mathison, Karin; Doherty, Kathleen
ABSTRACT: The development of dementia-friendly communities underpins inclusion and enablement of individuals to live well with dementia in communities for as long as possible. A number of strategies are being developed that present communities with models of "how to" become dementia-friendly. Communities are unique, with varying demographics, strengths, and resources that support local action. Indeed, the most valuable first step in the process of building a dementia-friendly community may be a targeted conversation within the community itself. To this end, four unique Australian communities participated in facilitated workshops to explore their collective dementia knowledge, visions for the future, community strengths, and possible actions to promote dementia-friendly initiatives. The diversity of communities that attended confirms that no single model of dementia-friendly communities should be imposed. A consultative-transformative approach to planning may meet the needs of specific communities and will focus responsibility and reward for implementation at the local and individual level.